On a Family of High-Order Iterative Methods under Kantorovich Conditions and Some Applications - S. Amat; C. Bermúdez; S. Busquier; M. J. Legaz; S. Plaza (Abstract and Applied Analysis)
This paper is devoted to the study of a class of high-order iterative methods for nonlinear equations on Banach spaces. An analysis of the convergence under Kantorovich-type conditions is proposed. Some numerical experiments, where the analyzed methods present better behavior than some classical schemes, are presented. These applications include the approximation of some quadratic and integral equations.